Luteinizing Hormone is an effective replacement for hCG to induce ovulation in Xenopus - Wlizla, Marcin (Dev Biol, 2016)
Injection of human Chorionic Gonadotropin (hCG) directly into the dorsal lymph sac of Xenopus is a commonly used protocol for induction of ovulation, but recent shortages in the stocks of commercially available hCG as well as lack of a well tested alternative have resulted in frustrating experimental delays in laboratories that predominantly use Xenopus in their research. Mammalian Luteinizing Hormones (LH) share structural similarity, functional equivalency, and bind the same receptor as hCG; this suggests that LH may serve as a good alternative to hCG for promoting ovulation in Xenopus. LH has been found to induce maturation of Xenopus oocytes in vitro, but whether it can be used to induce ovulation in vivo has not been examined. Here we compared the ability of four mammalian LH proteins, bovine (bLH), human (hLH), ovine (oLH), porcine (pLH), to induce ovulation in Xenopus when injected into the dorsal lymph sac of sexually mature females. We find that both ovine and human LH, but not bovine or porcine, are good substitutes for hCG for induction of ovulation in WT and J strain X. laevis and X. tropicalis.